Impact of Different Growing Media and Stem Cutting on the Growth and Yield of Bindu Lau (Lagenaria siceraria L.) - Ummeh Salma Binte Islam; Tahmina Mostarin; Khaleda Khatun; Khadijatul Cobra Karishma; Israt Jahan Kakoli; Suma Akter Labonno; Md. Jiad-Ur Rahaman; Md. Riad Mahmud; Mithila Farjana; Afra Nawar; Rabeya Tahshin Moon; Tasnia Thanim Mathin; et al. (Archives of Current Research International, 2025)
This study evaluated the influence of growing media and stem-cutting techniques on the growth, yield, and economic viability of Bindu Lau (Lagenaria siceraria L.). A Randomized Complete Block Design (RCBD) with three replications tested two factors: Factor A (growing media: M1 [Soil:FYM:Sand], M2 [Soil:Vermicompost:Sand], M3 [Soil:Kitchen Compost:Sand]) and Factor B (stem cuttings: P0 [control], P1 [pruning up to 90cm + top cutting], P2 [pruning up to 120cm + top cutting]). Among nine treatment combinations, M2 (vermicompost-based media) outperformed others, yielding 48.55 female flowers, 11.74 harvested branches, 40.44 fruits/plant, and 33.07 t/ha. P2 (120cm pruning + top cutting) maximized productivity with 50.22 female flowers, 42.22 fruits/plant, and 35.36 t/ha. The synergistic M2P2 combination achieved peak performance: 52.67 female flowers, 44.33 fruits/plant, and 37.17 t/ha yield, alongside the highest net income (737,382 Tk) and benefit-cost ratio (BCR: 2.28). Conversely, M1P0 (control) recorded the lowest outputs. Findings conclusively recommend M2P2 as the optimal strategy for enhancing Bindu Lau yield, growth, and profitability.